Symptoms of mental illness among university student-athletes during the second wave of the COVID-19 pandemic lockdown in Canada - Véronique Boudreault; Sophie Labossière; Véronique Gauthier; Sophie Brassard; Sophie Couture; Frédérick Dionne; Catherine Laurier; Natalie Durand-Bush (Frontiers Media S.A., 2022)
The COVID-19 pandemic lockdown disrupted the university sports season and had negative consequences on the academic and personal life of university student-athletes, resulting in several psychological challenges. The goal of this study is to document the symptoms of mental illness among university student-athletes during the second wave of the COVID-19 pandemic lockdown in Canada. It aims to (a) assess the prevalence of mental illness symptoms (anxiety, depression, disordered eating, and dangerous drinking) among university student-athletes and (b) identify which sociodemographic and sports characteristics, pandemic impacts, and levels of perceived stress most influence these symptoms. A total of 424 university student-athletes completed an online survey, which included questions on mental illness and the impact of the pandemic lockdown. The results revealed a notable prevalence of the symptoms of mental illness; depressive symptoms are reported by 37.9% of the participants, anxiety symptoms by 24.9%, dangerous drinking symptoms by 10.1%, and disordered eating by 8.6%. In addition, being female [OR = 0.56, 95% CI (0.33, 0.95)] or a member of a visible minority group [OR = 2.63, 95% CI (1.02, 6.78)] are significantly associated with the presence of depressive symptoms. Low academic motivation has a significant negative influence on the presence of depressive [OR = 3.37, 95% CI (1.82, 6.25)] and anxiety symptoms [OR = 2.75, 95% CI (1.35, 5.62)]. However, the presence of perceived stress was strongly associated with depressive [OR = 7.07, 95% CI (3.26, 15.35)], anxiety [OR = 6.51, 95% CI (3.30, 12.84)], and dangerous drinking symptoms [OR = 5.74, 95% CI (2.51, 13.14)]. This study advocates for specific mental illness prevention and treatment resources tailored to the unique needs of university student-athletes. Accordingly, partnerships and practical interventions to support university student-athletes' mental health are presented.